Discrepancies Between Clinical and Autopsy Diagnoses in Rapid Response Team–Assisted Patients: What Are We Missing?. Issue 7 (24th January 2022) - Giugni, Fernando Rabioglio; Salvadori, Fernanda Aburesi; Smeili, Luciana Andrea Avena; Marcílio, Izabel; Perondi, Beatriz; Mauad, Thais; de Paiva, Edison Ferreira; Duarte-Neto, Amaro Nunes
Abstract : Objectives: The rapid response team (RRT) assists hospitalized patients with sudden clinical deterioration. There is scarce evidence of diagnostic accuracy in this scenario, but it is possible that a considerable rate of misdiagnosis exists. Autopsy remains a valuable tool for assessing such question. This study aimed to compare clinical (premortem) and autopsy (postmortem) diagnoses in patients assisted by the RRT and describe major discrepancies. Methods: We reviewed 104 clinical data and autopsies from patients assisted by the RRT during a cardiac arrest event in a tertiary care hospital in Brazil. Clinical and autopsy diagnostic discrepancies were classified using the Goldman criteria. Other clinical and pathological data were described, and the group with major diagnostic discrepancies was further analyzed. Results: We found 39 (37.5%) patients with major diagnostic discrepancies. Most frequent immediate causes of death in this group determined by autopsy were sepsis (36%), pulmonary embolism (23%) and hemorrhagic shock (21%). Pulmonary embolism was the cause of death significantly more frequent in the major discrepancy group than in the minor discrepancy group (23% versus 3%, P = 0.002). We individually described all major diagnostic discrepancies. Conclusions: We found a high rate (37.5%) of major misdiagnosis in autopsies from patients assisted by the RRT in a tertiary teaching hospital. Pulmonary embolism was the most inaccurate fatal diagnosis detected by autopsy.